1992
DOI: 10.1099/00221287-138-5-849
|View full text |Cite
|
Sign up to set email alerts
|

D-Alanyl-lipoteichoic acid in Lactobacillus casei: secretion of vesicles in response to benzylpenicillin

Abstract: Vesicles containing lipoteichoic acid (LTA) have been isolated from Lactobacillus casei ATCC 7469 grown in the presence of either benzylpeniciUin or D-cycloserine. These cell wall antibiotics enhanced the rate of LTA and lipid secretion 6.7 times, whereas chloramphenicol inhibited their release. The formation of these vesicles from peripheral and septal wall regions did not appear to be the result of bacteriolysis. The vesicle composition of LTA and lipid was similar to that of the cytoplasmic membrane whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…The chain length of poly(Gro-P) (Fig. 3B) varies from 14 to 33 and from 5 to 50 Gro-P units in LTA isolated from Enterococcus faecalis and Lactobacillus rhamnosus ATCC 7469, respectively (301,394). The polydispersity of LTA in these organisms confirmed that observed originally in Streptococcus agalactiae (331).…”
Section: Structures Of Wta and Ltasupporting
confidence: 64%
“…The chain length of poly(Gro-P) (Fig. 3B) varies from 14 to 33 and from 5 to 50 Gro-P units in LTA isolated from Enterococcus faecalis and Lactobacillus rhamnosus ATCC 7469, respectively (301,394). The polydispersity of LTA in these organisms confirmed that observed originally in Streptococcus agalactiae (331).…”
Section: Structures Of Wta and Ltasupporting
confidence: 64%
“…pennsylvanicum resulted in an increase of lipoglycan excretion (33). This was not the result of bacteriolysis, as was also observed for acylated or deacylated LTAs of other bacteria and for other inhibitors of cell wall synthesis (33,35,43,49). Consequently, antibiotic treatment of immunocompromised patients will increase the free lipoglycan pool in the intestine which may easily translocate to the blood.…”
Section: Discussionmentioning
confidence: 93%
“…The macroamphiphiles are secreted even during normal growth both with and without their lipid anchor. Secretion is stimulated by exposure to ␤-lactam antibiotics (9,12,33,35). In aqueous solutions, the acylated molecules form micellar aggregates (53).…”
mentioning
confidence: 99%
“…These results highlight a strain and stimulus-dependent protection by LB, which we suggest is enhanced for L. plantarum and L. salivarious against NmB by a factor secreted in their conditioned medium (Figure 2). In our study inflammatory attenuation by their conditioned medium was largely independent of TLR-2 (Figure 3), in contrast to others [40], so is unlikely to involve LB lipoteichoic acid, which can be shed in vesicles by some strains [41] and is highly anti-inflammatory [42,43].…”
Section: T L Bekele Et Almentioning
confidence: 99%